(untitled) (Research, Society and Development, 2025)
Sexually Transmitted Infections (STIs) persist as a health problem, highlighting the need to promote and prevent infections in special groups, such as military police officers. This article aims to present research on rapid testing actions for HIV, syphilis, and hepatitis among military police officers of the North Area Policing Command (CPA) in Manaus, Amazonas State. The outreach activity, developed by students of the Nursing course at the FAMETRO University Center – North, involved the spontaneous invitation of participants, collection of basic information, and application of rapid tests according to standardized protocols, covering police officers of different age groups and genders. The results showed that 45 police officers underwent rapid tests for the detection of hepatitis B and C, HIV, and syphilis; 100% of the samples were negative, demonstrating positive results in infection prevention. The action contributes to expanding and reinforcing the importance of prevention and consolidating the link between health services and the local population.